Decreased Oxidative Stress in Male Patients with Active Phase Ankylosing Spondylitis Who Underwent Whole-Body Cryotherapy in Closed Cryochamber. (2nd May 2018) - Stanek, Agata; Cholewka, Armand; Wielkoszyński, Tomasz; Romuk, Ewa; Sieroń, Aleksander
Abstract : Objective . The aim of the study was to estimate the impact of whole body cryotherapy (WBC) on oxidative stress when performed in a closed cryochamber on patients with ankylosing spondylitis (AS). Material and methods . The effect of ten WBC procedures lasting 3 minutes a day with a subsequent 60-minute session kinesiotherapy on oxidative stress in male AS patients (WBC group n = 16 ) was investigated. To assess the disease activity, the Bath Ankylosing Spondylitis Diseases Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) were calculated. The WBC group was compared to the kinesiotherapy only (KT; n = 16 ) group. The routine parameters of oxidative stress (antioxidant enzymatic and nonenzymatic antioxidant status, lipid peroxidation products, total oxidative status (TOS), and oxidative stress index (OSI)) were estimated one day before the beginning and one day after the completion of the research program. Results . After the completion of the treatment in the WBC group, a significant decrease of oxidative stress markers (TOS and OSI) and a significant increase of total antioxidant status were observed. The erythrocyte activity of glutathione peroxidase, glutathione reductase decreased significantly in both groups, but the differences of activity of that enzymes prior to post treatment values (Δ) in the KT group were significantly higher as compared to the WBC group. The activity of erythrocyte catalase and plasma ZnCu isoenzyme of superoxide dismutase showed a decreased tendency; erythrocyte total superoxide dismutase activity showed an increased tendency in the WBC group after the completion of the treatment. The BASDAI and BASFI decreased significantly in both groups, but the differences of value indexes prior to post treatment (Δ) were significantly higher in the WBC than KT group. Conclusion . WBC performed in a closed cryochamber decreases oxidative stress and improves BASDAI and BASFI indexes in male patients during the active phase of ankylosing spondylitis.